Biochemical and Cellular Analysis of Human Variants of the DYT1 Dystonia Protein, TorsinA/TOR1A. Issue 9 (17th July 2014) - Hettich, Jasmin; Ryan, Scott D.; de Souza, Osmar Norberto; Saraiva Macedo Timmers, Luís Fernando; Tsai, Shelun; Atai, Nadia A.; da Hora, Cintia C.; Zhang, Xuan; Kothary, Rashmi; Snapp, Erik; Ericsson, Maria; Grundmann, Kathrin; et al.
ABSTRACT Early‐onset dystonia is associated with the deletion of one of a pair of glutamic acid residues (c.904_906delGAG/c.907_909delGAG; p.Glu302del/Glu303del; ΔE 302/303) near the carboxyl‐terminus of torsinA, a member of the AAA+ protein family that localizes to the endoplasmic reticulum lumen and nuclear envelope. This deletion commonly underlies early‐onset DYT1 dystonia. While the role of the disease‐causing mutation, torsinAΔE, has been established through genetic association studies, it is much less clear whether other rare human variants of torsinA are pathogenic. Two missense variations have been described in single patients: R288Q (c.863G>A; p.Arg288Gln; R288Q) identified in a patient with onset of severe generalized dystonia and myoclonus since infancy and F205I (c.613T>A, p.Phe205Ile; F205I) in a psychiatric patient with late‐onset focal dystonia. In this study, we have undertaken a series of analyses comparing the biochemical and cellular effects of these rare variants to torsinAΔE and wild‐type (wt) torsinA to reveal whether there are common dysfunctional features. The results revealed that the variants, R288Q and F205I, are more similar in their properties to torsinAΔE protein than to torsinAwt. These findings provide functional evidence for the potential pathogenic nature of these rare sequence variants in the TOR1A gene, thus implicating these pathologies in the development of dystonia.